Enzymatic hydrolysis of starch from the anthocyanin extraction residue (AER-starch) with ultrasound pretreatment: A techno-economic assessment - J.D. Quiñonez-Ensuncho; Susana Ochoa; Víctor-Manuel Osorio-Echeverri; J. Felipe Osorio-Tobón (PLoS ONE, 2026)
Purple yam ( Dioscorea alata ) is a tropical tuber crop that is a source of anthocyanins and starch. Starch can be isolated from the large quantity of extraction residues and become a raw material for hydrolyzate production. Ultrasound pretreatment was evaluated in consecutive enzymatic hydrolysis (UCEH) and simultaneous enzymatic hydrolysis (USEH) of starch from anthocyanin extraction residue (AER-starch). A techno-economic assessment was performed. Ultrasound pretreatment showed a positive influence on CEH and SEH. The hydrolysis degree (HD) was higher in CEH (72.87 ± 3.01%) than in SEH (28.10 ± 1.32%). CEH performed better than SEH, primarily due to the thermal instability of the enzymes. Enzymatic hydrolysis solubilized almost all AER-starch. Starch conversion (SC) above 90% was achieved for all CEH experiments using AER-starch concentrations ranging from 10 to 50 g L -1 . The cost of manufacturing (COM) for glucose syrup using AER concentrations of 10 and 350 g L -1 was US$61.25 kg −1 and US$2.90 kg −1 , respectively, when the purchasing cost for AER-starch was US$1.50 kg −1 . The CRM was the major component of the COM (above 50%) when AER-starch concentrations were higher than 100 g L -1 , AER-starch being the primary raw material contributing to the COM. The production of the glucose syrup was economically feasible when the AER-starch purchasing price was under US$1.20 kg -1 and the selling price was at least US$3.50 kg -1 .